Performance Evolution of Intrusion Detection system on MANET Using Genetic Evolution - Singh, Kirti; Yadav, Poonam (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Mobile ad hoc networks (MANETs) are one of the best ever growing areas of research. By providing communications in the absence of fixed infrastructure MANETs are an attractive technology. However this edibility introduces new security threats. The traditional way of protecting networks is not directly applicable to MANETs. Many conventional security solutions are ineffective and inefficient for the highly dynamic and resource-constrained environments where MANET use might be expected.Â  In this paper we solving security issue in Mobile Adhoc Network using Evolutionary Computation that will be discover complex properties of mobile ad hoc networks and evolve intrusion detection programs suitable for this new environment. Programs evolved using Grammatical Evolution techniques which is part of Evolutionary Computation, will be able to detect specific routing attacks on mobile ad hoc networks.